Efektivitas Ekstrak Daun Pandan Wangi (Pandanus Amaryllifolius) Terhadap Daya Tahan Larva Anopheles Sp. - Tusy Triwahyuni; Ismalia Husna; Devita Febriani; Ihsanul Karim (Universitas Malahayati Lampung, 2021)
ABSTRACT Background of study: Malaria is a life-threatening disease caused by the Protozoa parasite Plasmodium genus. This disease is transmitted to humans through the bite of the Anopheles sp. The Southeast Asian region is also a concern for malaria cases. There are 1.4 billion people at risk of malaria and 352 million at high risk . Malaria cases in Southeast and South Asia are in 10 countries, namely East Timor, Sri Lanka, Butan, Bangladesh, Thailand, South Korea, Nepal, Myanmar, India and Indonesia. Indonesia is a country that is very rich in biodiversity. Among the thousands of plants that grow in Indonesia, there are various plants that are unique and have multiple functions. Pandan leaves (Pandanus amaryllifolius) is a plant that can be used as a natural insecticide, because it is effective in controlling insects (mosquitoes).Objective: The purpose of the study was to determine the effectiveness of pandanus amaryllifolius leaf extract on the resistance of Anopheles larvae.Research Methods: This type of research is an experiment with a completely randomized design research (RAL).Research Results: The average mortality percentage of the highest larvae with a concentration of 1000 ppm reached 94%, the percentage concentration of 800 ppm reached 90%, the percentage concentration of 600 ppm reached 80% and the lowest concentration of 400 ppm reached 60%. Results were obtained from mortality rates.Conclusion: There is the effect of fragrant pandan leaf extract on the durability of Anopheles sp. Larvae. With the highest concentration of 1000 ppm (94%) with the number of deaths of 19 larvae, the lowest percentage concentration of 400 ppm (60%) with the number of deaths of 14 Anopheles sp. larvae. Keywords: Pandan Leaves (Pandanus amaryllifolius) , Larval mortality, Anopheles sp. ABSTRAK Latar Belakang: Malaria adalah penyakit mengancam jiwa yang disebabkan oleh parasit Protozoa genus Plasmodium. Penyakit ini ditularkan ke manusia melalui gigitan nyamuk Anopheles Sp. Kawasan Asia Tenggara juga menjadi perhatian kasus malaria. Terdapat 1,4 miliar penduduk berisiko terkena malaria dan 352 juta pada risiko tinggi. Kasus malaria di Asia Tenggara dan Selatan terdapat di 10 negara yakni Timor Leste, Sri Lanka, Butan, Bangladesh, Thailand, Korea Selatan, Nepal, Myanmar, India dan Indonesia. Indonesia merupakan negara yang sangat kaya akan keanekaragaman hayati. Di antara ribuan tanaman yang tumbuh di Indonesia, terdapat berbagai tanaman yang unik dan memiliki fungsi ganda. Tanaman daun pandan wangi (Pandanus Amaryllifolius) merupakan salah satu tanaman yang dapat digunakan sebagai insektisida alami, karena efektif pengendalikan serangga (nyamuk).Tujuan: Tujuan dari penelitian adalah untuk mengetahui efektifitas ekstrak daun pandan wangi terhadap daya tahan larva Anopheles Sp.Metode Penelitian: Jenis Penelitian ini adalah eksperimen dengan desain penelitian rancangan acak lengkap (RAL).Hasil Penelitian: Didapatkan rata-rata mortalitas persentase larva tertinggi dengan konsentrasi 1000 ppm mencapai 94%, persentase konsentrasi 800 ppm mencapai 90%, persentase konsentrasi 600 ppm mencapai 80% dan konsentrasi terendah 400 ppm mancapai 60%. Hasil diperoleh dari rata-rata mortalitas.Kesimpulan: Terdapat pengaruh ekstrak daun pandan wangi terhadap daya tahan larva Anopheles Sp. Dengan konsentrasi paling tinggi 1000 ppm (94%) dengan jumlah kematian 19 larva, persentase konsentrasi terendah 400 ppm (60%) dengan jumlah kematian 14 larva Anopheles Sp. Kata Kunci: Daun Pandan Wangi (Pandanus amaryllifolius), Mortalitas Larva, Anopheles Sp. Kepustakaan : 29 (2007-2018).